Tooth and Gingival Display at Posed and Spontaneous Smile - Devkota, G; Pradhan, S Joshi; Shrestha, P; Sah, S; Verma, A (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Amount of gingival display is one of the important aspect of smile esthetics parameter which allows the clinician to accurately diagnose and select an appropriate treatment plan for the patient. The purpose of this study is to evaluate the amount of teeth and gingival display in posed and spontaneous smile by using videography method.Methodology: A cross-sectional, observational study was conducted among 144 participants. Standardized videography of the participants were taken with DSLR. Video clips were taken for tooth display at rest, posed smile and spontaneous smile. Digital recordings were transferred to laptop and measurements of the dentogingival display were made by importing frames in Adobe photoshop CS6 extended software. The type of smile line were recorded based on the dentogingival display at posed and spontaneous smile. Data were entered and analyzed in excel 2016. Parametric (quantitative) data were interpreted as mean ± SD and Non parametric (qualitative) data were interpreted as percentile. To compare parametric data student t test was used and for non parametric data chi square test was used.Result: There was a significant difference between dentogingival display during posed and spontaneous smile. In male participants, the mean tooth display at rest was 0.91 mm, mean dentogingival display at posed smile was 7.21 mm and at spontaneous smile was 9.02 mm. In female participants, the mean tooth display at rest was 1.26 mm, mean dentogingival display at posed smile was 7.39 mm and at spontaneous smile was 9.48 mm.Conclusion: Within the limitations of this study, dentogingival display in spontaneous smiles is higher than in posed evaluations. Clinical evaluations and restorative thoughts should be planned according to the spontaneous smile, as the gingival appearance increases when patients are smiling naturally rather than posing. Video recordings provides more comprehensive information for assessment of dentogingival display.